1990
DOI: 10.2118/18856-pa
|View full text |Cite
|
Sign up to set email alerts
|

An Analytical Model for History Matching Naturally Fractured Reservoir Production Data

Abstract: This paper presents a method for analyzing production data from naturally fractured gas reservoirs. A normalized time is used to modify analytical solutions to model gas flow in finite, dual-porosity reservoirs. Procedures for validating the dual-porosity reservoir model, determining the suitability of simpler reservoir models, and determining the best parameter estimates are illustrated with field data from naturally fractured reservoirs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
2
0

Year Published

1992
1992
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The dual-media model is widely used in the characterization of porous media (Warren and Root 1963;De 1976;Su et al 2016a, b). It is found that the porous media is mainly composed of fractures and matrix, which is also a widely recognized and adopted continuum model.…”
Section: Multi-scale Media Model and Domain Divisionmentioning
confidence: 99%
See 1 more Smart Citation
“…The dual-media model is widely used in the characterization of porous media (Warren and Root 1963;De 1976;Su et al 2016a, b). It is found that the porous media is mainly composed of fractures and matrix, which is also a widely recognized and adopted continuum model.…”
Section: Multi-scale Media Model and Domain Divisionmentioning
confidence: 99%
“…As research scholars continue to study shale gas transport laws in the subsurface, the analytical method can better describe the transport mechanisms in different stages of shale gas development. Based on the equivalent continuous media model, many scholars defined the relationship among artificial fractures, secondary extension fractures, natural fractures, inorganic matrix, and organic kerogen matrix in shale reservoirs (Warren and Root 1963;De 1976;Watson et al 1990;Wu et al 2009;Swami and Settari 2012;Urban et al 2017;Guo and Yang 2019;Mohamed et al 2021). They discovered the existence of gas-water two-phase flow, trilinear, and five-linear flow patterns between different flow regions (Bello and Wattenbarger 2010;Brown et al 2009;Ozkan et al 2010;Brohi et al 2011;Ozkanet et al 2011;Stalgorova and Mattar 2012a, b;Yin et al 2015;Zhang et al 2015;Fan and Ettehadtavakkol 2016;Su et al 2016a, b;Zeng et al 2019;Liu et al2020;Behmanesh et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Reservoir numerical simulation study was put forward in the middle of the 20 th century. Watson, et al used ideal dual porosity medium model to do numerical simulation of shale capacity [11]. Bustin studied the effects of crack spacing and matrix diffusion on shale capacity [12].…”
Section: Introductionmentioning
confidence: 99%
“…Watson et al (1990) performed a history match of the production data of a naturally fractured gas reservoir. In their method a normalized time was used to modify the analytical solutions to model gas flow in finite, dual-porosity reservoirs.…”
Section: Introductionmentioning
confidence: 99%